Disruption of BMP Signaling Prevents Hyperthyroidism‐Induced Bone Loss in Male Mice. (15th June 2020) - Lademann, Franziska; Weidner, Heike; Tsourdi, Elena; Kumar, Ravi; Rijntjes, Eddy; Köhrle, Josef; Hofbauer, Lorenz C; Rauner, Martina
ABSTRACT: Thyroid hormones (TH) are key regulators of bone health, and TH excess in mice causes high bone turnover–mediated bone loss. However, the underlying molecular mechanisms of TH actions on bone remain poorly defined. Here, we tested the hypothesis whether TH mediate their effects via the pro‐osteogenic bone morphogenetic protein (BMP) signaling pathway in vitro and in vivo. Primary murine osteoblasts treated with 3, 3′, 5‐triiodo‐L‐thyronine (T3 ) showed an enhanced differentiation potential, which was associated with activated canonical BMP/SMAD signaling reflected by SMAD1/5/8 phosphorylation. Blocking BMP signaling at the receptor (LDN193189) and ligand level (noggin, anti‐BMP2/BMP4 neutralizing antibodies) inhibited T3 ‐induced osteogenic differentiation. In vivo, TH excess over 4 weeks in male C57BL/6JRj mice led to severe trabecular bone loss with a high bone turnover that was completely prevented by treatment with the BMP ligand scavenger ALK3‐Fc. Thus, TH activate the canonical BMP pathway in osteoblasts to promote their differentiation and function. Importantly, this study indicates that blocking the BMP pathway may be an effective strategy to treat hyperthyroidism‐induced bone loss. © 2020 The Authors. Journal of Bone and Mineral Research published by American Society for Bone and Mineral Research.